Climate Smart Agriculture Practices: A Synthesis of Implementation in Nigeria - Chibuzo U. Izuogu; Joy O. Oparaojiaku; Michael O. Olaolu; Susan C. Iroegbu; John O. Ifabiyi; Janet B. Ayegboyin; Abraham G. Ominikari (Journal of Agriculture and Environment for International Development)
The impact of climate is threatening sustainable food production worldwide. Climate-smart agriculture (CSA) is a strategic practice that supports farming, ameliorates food insecurity, and advances sustainable agriculture. This study assesses the implementation of CSA through the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). From an initial in-depth search of 337 publications, 98 articles fulfilled the inclusion criteria. Results showed that awareness of CSA remains low even with a steady increase in publications from 2020-2023. The south-western region was the most studied as farmers implemented various approaches across the country with 43% of the studies highlighting the implementation of indigenous knowledge which includes adjusting the planting dates and use of natural pest control methods. Major determinants of the adoption of CSA were access to credit, contact with extension service providers, years of farming experience, and level of education. Farmers recorded an increase in production and income with improvement in soil health due to their adoption of CSA. The absence of government policies, the high cost of implementation, and low level of technical skill were hindrances to the adoption of CSA. The study concludes that farmers in Nigeria are implementing CSA practices. There is a need to increase awareness and develop the capacity of farmers through training in CSA skills. The government should legislate reforms and provide incentives to support farmers to adopt CSA.